Effects of extraction time on the functional properties of silver catfish (Pangasius sutchi) skin gelatin / Normah Ismail, Najihah Shukor and Zainal Samicho - Ismail, Normah; Shukor, Najihah; Samicho, Zainal (Research Management Institute (RMI), 2013)
Silver catfish (Pangasius sutchi) skin gelatin was extracted to determine the effects of extraction time on the functional properties of the gelatin in terms of solubility, protein solubility as a function of pH and sodium chloride concentration, emulsifying capacity and stability, water holding capacity, fat binding capacities and foaming properties. Silver catfish skins were washed in sodium chloride (NaCl) solution prior to pre-treatment in sodium hydroxide (NaOH) and acetic acid solution. Gelatin was extracted at 50ºC for 6, 8, 10 and 12 hours extraction time followed by freeze drying. The extraction of silver catfish skin gelatin at 50 ºC for 12 hours was more effective than extraction at 6, 8 and 10 hours where the gelatin was characterized by higher emulsifying capacity (52.63%), emulsifying stability (47.83%), water holding capacity (31.78 mL/g), fat binding capacities (54.76%), foaming capacity (41.47 mL) and foaming stability (56.42%) than gelatins extracted at other extraction time. The longer the extraction time, the better the functional properties of the gelatin. Based on its good functional properties, silver catfish skin gelatin may be useful in various food applications such as soups, sauces and gravies.